Anterior Cruciate Ligament Reconstruction With Concomitant Meniscal Repair: Is Graft Choice Predictive of Meniscal Repair Success?. Issue 9 (13th September 2021) - Salem, Hytham S.; Huston, Laura J.; Zajichek, Alexander; McCarty, Eric C.; Vidal, Armando F.; Bravman, Jonathan T.; Spindler, Kurt P.; Frank, Rachel M.; Amendola, Annunziato; Andrish, Jack T.; Brophy, Robert H.; et al.
Background: When meniscal repair is performed during anterior cruciate ligament (ACL) reconstruction (ACLR), the effect of ACL graft type on meniscal repair outcomes is unclear. Hypothesis: The authors hypothesized that meniscal repairs would fail at the lowest rate when concomitant ACLR was performed with bone–patellar tendon–bone (BTB) autograft. Study Design: Cohort study; Level of evidence, 3. Methods: Patients who underwent meniscal repair at primary ACLR were identified from a longitudinal, prospective cohort. Meniscal repair failures, defined as any subsequent surgical procedure addressing the meniscus, were identified. A logistic regression model was built to assess the association of graft type, patient-specific factors, baseline Marx activity rating score, and meniscal repair location (medial or lateral) with repair failure at 6-year follow-up. Results: A total of 646 patients were included. Grafts used included BTB autograft (55.7%), soft tissue autograft (33.9%), and various allografts (10.4%). We identified 101 patients (15.6%) with a documented meniscal repair failure. Failure occurred in 74 of 420 (17.6%) isolated medial meniscal repairs, 15 of 187 (8%) isolated lateral meniscal repairs, and 12 of 39 (30.7%) of combined medial and lateral meniscal repairs. Meniscal repair failure occurred in 13.9% of patients with BTB autografts, 17.4% of patients with soft tissue autografts, and 19.4% of patients with allografts. The odds of failure within 6 years of index surgery were increased more than 2-fold with allograft versus BTB autograft (odds ratio = 2.34 [95% confidence interval, 1.12-4.92]; P = .02). There was a trend toward increased meniscal repair failures with soft tissue versus BTB autografts (odds ratio = 1.41 [95% confidence interval, 0.87-2.30]; P = .17). The odds of failure were 68% higher with medial versus lateral repairs ( P < .001). There was a significant relationship between baseline Marx activity level and the risk of subsequent meniscal repair failure; patients with either very low (0-1 points) or very high (15-16 points) baseline activity levels were at the highest risk ( P = .004). Conclusion: Meniscal repair location (medial vs lateral) and baseline activity level were the main drivers of meniscal repair outcomes. Graft type was ranked third, demonstrating that meniscal repairs performed with allograft were 2.3 times more likely to fail compared with BTB autograft. There was no significant difference in failure rates between BTB versus soft tissue autografts. Registration: NCT00463099(ClinicalTrials.gov identifier).